Co-Mnt lamellar membranes for ultrafast activation of peroxymonosulfate via a nonradical pathway - Yunpu Zhao; Xiaoyan Li; Yi Zhou; Ruoxi Liu; Xiaotong Yang; Sijia Sun; Guocheng Lv; Libing Liao (Journal of Environmental Chemical Engineering, 2026)

Numerical oscillations and minimum time-step size in coupled thermo-hydro-mechanical finite element analysis of saturated porous media - Libing Han; Wentao Li; Changfu Wei (Computational Geosciences, 2026)

Responses of Processing Tomato Growth and the Soil Microenvironment to Micro‐Nano Aeration and Humic Acid Application Under Warming Drip Irrigation - Chubo Wang; Liang Li; Yongting Zhu; Zhiyu Chai; Qixiang Zhou; Yuhang Lu; Yan Zhu; Libing Song; Jiaying Ma (Irrigation and Drainage, 2026)
Plastic‐mulched drip irrigation is widely used in arid regions, but it may aggravate root‐zone hypoxia and salinity. A two‐year field experiment based on two two‐factor designs was conducted in Xinjiang, China, during 2023 and 2024 to investigate the combined effects of irrigation‐water temperature (10°C–15°C and 20°C–25°C), aeration method (5 mg L −1 (no aeration)) and 18 mg L −1 (micro‐nano aeration) and humic acid application (0 and 0.5% of fertigation mass) on processing tomato growth, yield, fruit quality, root‐zone soil conditions and greenhouse gas fluxes. Micro‐nano aeration and humic acid significantly increased yield and improved fruit quality, with maximum yields of 198.1–205.9 t ha −1 . Irrigation‐water warming increased single fruit weight by 4% and soluble sugar content by 8%–10%. These responses were associated with improved soil oxygen and water availability and reduced effective salinity. Aeration and humic acid increased CO 2 and N 2 O emissions but also promoted CH 4 uptake. Structural equation modelling showed that soil oxygen and temperature were the main drivers of plant growth and lycopene accumulation. The combined application of warmed irrigation water, micro‐nano aeration and humic acid was an effective strategy for improving processing tomato production in arid regions.

Tuning CO2 separation of Type I UiO-66 porous liquids by varying the size of porous hosts - Shuangshuang Long; Jingwen Wang; Shuqian Meng; Yaxin Liu; Jing Zhang; Zihao Ren; Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Libing Qian; Wenwu Zhou; et al. (Journal of Environmental Chemical Engineering, 2026)

Clay minerals in electrochemical technologies: Recent advances in energy storage and electrocatalysis applications - Jiaxing Han; Meng Liu; Tianming Liu; Libing Liao; Ritong Huang; Wenfeng Li; Guocheng Lv (Applied Clay Science, 2026)

Hydroxyapatite nanowires enhanced biochar hybrid aerogel for superior Ni(II) adsorption - Ting Wang; Haiyan Wu; Yili Wang; Yuansong Wei; Dunqiu Wang; Haixiang Li; Yufeng Xu; Libing Zheng (Journal of Cleaner Production, 2026)

Polyethylene and polylactic acid microplastics affect the migration of Cr(VI) and Cr(III) in acidic clay soil via distinct mechanisms - Weiming Feng; Gongwei Xu; Xinru Zhai; Libing Zheng; Helian Li (Environmental Pollution, 2026)

Research on sample preparation of calcareous and silica sand with air pluviation method - Ruiming Liu; Libing Li; Naman Maimaiti; Peng Chen (Marine Georesources & Geotechnology, 2026)

Reliability analysis of CRTS III slab ballastless track structure on bridge based on probability density evolution - Li Song; Libing Chen; Maodong Zhu; Wenchang Zhang; Jian Hou (Engineering Structures, 2026)

Virtual screening and activity evaluation of novel ecdysone analogues targeting overlapping binding pockets in Lepidoptera ecdysone receptor - Yanjiao Feng; Jialin Cui; Hongyan Wang; Qinyan Tan; Shangzhong Liu; Libing Liu; Li Zhang (Pesticide Biochemistry and Physiology, 2026)

Pulsed light delays the softening of apricot fruit by modulating pectin lyase (PL) activity - Mengpei Liu; Wanrui Li; Libing Zhang; Xiaopeng Wei; Chenyang Wu; Haifei Lu (Food Bioscience, 2025)

Prediction of water quality in the middle area of Yangtze River using efficient machine learning model - Jingjing Xia; Wenya Chen; Libing Liu; Ziyan Li; Yutong Wang; Chaohao Yang; Jin Zeng (Environmental Geochemistry and Health, 2025)

Underwater light limitation controls long-term submerged plant persistence in Lake Poyang floodplains, an important Ramsar site - Qian Hu; Wenkai Li; Aiwen Zhong; Songhe Jiang; Libing Liao; Lei Xu; Liqiao Tian (Journal of Environmental Management, 2025)

One-step dual-functional modification of Ni-rich cathodes via DFT prediction for high-rate quasi-solid-state batteries - Yunting Wang; Gaohui Du; Di Han; Weihao Shi; Liming Wang; Libing Yao; Huayu Li; Jingyi Jing; Shaochen Wei; Shixian Chen; Wenqi Zhao; Qingmei Su (Chemical Engineering Journal, 2025)

Lead concentration derives phase alteration of hydroxylapatite - Lingchang Kong; Xin Liu; Tianming Liu; Baogang Zhang; Hao Liu; Zhaohui Li; Guocheng Lv; Libing Liao (Applied Geochemistry, 2025)

Development and application of a dual RT-qPCR assay for differentiating of goose astrovirus genotypes 1 and 2 - Wenyang Liu; Jinfeng Wang; Libing Liu; Xiaoxia Sun; Longhai Ji; Wanzhe Yuan; Binglei Cao; Xincheng Ji; Ruiwen Li; Jianchang Wang (Research in Veterinary Science, 2025)

Optimizing woody oil biodiesel production in yellowhorn via phenotypic marker development: a study of trait–index associations and germplasm screening - Wei Zhang; Linkun Li; Puxia Wu; Hui Yang; Huihui Xu; Quanxin Bi; Changchun Shi; Libing Wang (Journal of Plant Physiology, 2025)

Simultaneous Detection of HEV, HAstV and SaV in Bivalve Shellfish Using a Novel Real-Time RT-qPCR Method - Yan Wang; Jinfeng Wang; Yujing Li; Maolin Wei; Wei Wang; Libing Liu; Bolong Liang; Xiangdong Xu; Jianchang Wang (Food and Environmental Virology, 2025)

Characteristics and Evaluation of Living Shorelines: A Case Study from Fujian, China - Xingfan Li; Shihui Lin; Libing Qian; Zhe Wang; Chao Cao; Qi Gao; Jiwen Cai (Journal of Marine Science and Engineering, 2025)
Under the context of global climate change, sea-level rise and frequent storm surge events pose significant challenges to coastal areas. Protecting coastlines from erosion, mitigating socio-economic losses, and maintaining ecosystem balance are critical for the sustainable development of coastal zones. The concept of “living shorelines” based on Nature-based Solutions (NbS) employs near-natural ecological restoration and protection measures. In low-energy coastal segments, natural materials are prioritized, while high-energy segments are supplemented with artificial structures. This approach not only enhances disaster resilience but also preserves coastal ecosystem stability and ecological functionality. This study constructs a coastal vitality evaluation system for Fujian Province, China, using the entropy weight method, integrating three dimensions: protective safety, ecological resilience, and economic vitality. Data from 2010 and 2020 were analyzed to assess the spatiotemporal evolution of coastal vitality. Results indicate that coastal vitality initially exhibited a spatial pattern of “low in the north, high in the center, and low in the south,” with vitality values ranging from 0.20 to 0.67 (higher values indicate stronger vitality). Over the past decade, ecological restoration projects have significantly improved coastal vitality, particularly in central and southern regions, where high-vitality segments increased markedly. Key factors influencing coastal vitality include water quality, cyclone intensity, biological shoreline length, and wetland area. NbS-aligned coastal management strategies and soft revetment practices have generated substantial ecological and economic benefits. To further enhance coastal vitality, region-specific approaches are recommended, emphasizing rational resource utilization, optimization of ecological and economic values, and the establishment of a sustainable evaluation framework. This study provides scientific insights for improving coastal protection capacity, ecological resilience, and economic potential.

Corrigendum to “Design, hydrodynamic analysis, and test of a manta ray-inspired soft wing for flapping wing propulsion of underwater gliders” [Ocean Eng. 327 (2025) 120998] - Yudong Guo; Yuting Li; Xiao Yu; Libing Han; Wendong Niu; Tongshuai Sun (Ocean Engineering, 2025)

A Dirac δ function based frequency-domain algorithm for the offshore structural vibration considering non-zero initial conditions - Dongan Li; Shengli Chen; Libing Zou; Xiang Yuan Zheng (Ocean Engineering, 2025)

Corrigendum to “Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption” [Chem. Eng. J. 500 (2024) 156655] - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2025)

Vegetation type and Fe and Al oxides are important factors influencing the spatial distributions of soil organic carbon and mineral-associated organic carbon in mountain ecosystems - Wenzhi Zhou; Suyan Li; Xiangyang Sun; Rongsong Zou; Libing He; Jiantao Yu; Guanyu Zhao (Geoderma Regional, 2025)

Dynamic landslide susceptibility mapping on time-series InSAR and explainable machine learning: a case study at Wushan in the Three Gorges Reservoir area, China - Na Lin; Kai Ding; Libing Tan; Boyuan Li; Kai Yang; Chun Wang; Bin Wang; Nanjie Li; Ronghua Yang (Advances in Space Research, 2025)

Design, hydrodynamic analysis, and test of a manta ray-inspired soft wing for flapping wing propulsion of underwater gliders - Yudong Guo; Yuting Li; Xiao Yu; Libing Han; Wendong Niu; Tongshuai Sun (Ocean Engineering, 2025)

Integrative proteogenomic and pharmacological landscape of acute myeloid leukaemia - Hanlin Wang; Jun-Yu Xu; Tao Wang; Gaoya Xu; Guanghao Luo; Mingya Zhang; Gusheng Tang; Chang Wang; Libing Wang; Weijia Fu; Xiong Ni; Linhui Zhai; et al. (Science Bulletin, 2025)

A NH2-UiO-66-TiO2/Al2O3 hollow ceramic membrane with an enhanced photocatalytic oxidation performance of NO - Wenjuan Yang; Wenli Liu; Yuanbo Song; Yangyang Wang; Yanbin Yun; Guicheng Liu; Chang Li; Jiaming Mao; Jia Liu; Meng Li; Chunyun Zhou; Manxiang Wang; et al. (Journal of Environmental Chemical Engineering, 2025)

Dry-processing of VN quantum dots/N, O, S-doped hierarchical porous carbon electrodes with high sulfur-loading for practical lithium-sulfur batteries - Shixian Chen; Gaohui Du; Yan Cheng; Di Han; Jiahao Deng; Yunting Wang; Huayu Li; Libing Yao; Dong Wang; Qingmei Su; Bingshe Xu (Chemical Engineering Journal, 2025)

Pilot work of the 10K Chinese People Genomic Diversity Project along the Silk Road suggests a complex east-west admixture landscape and biological adaptations - Guanglin He; Hongbing Yao; Shuhan Duan; Lintao Luo; Qiuxia Sun; Renkuan Tang; Jing Chen; Zhiyong Wang; Yuntao Sun; Xiangping Li; Liping Hu; Libing Yun; et al. (Science China Life Sciences, 2025)

A novel theoretical approach to calculate critical normalized roughness Rcr at the soil-structure interface - Ruiming Liu; Tong Dong; Fuxian Jian; Libing Li (Computers and Geotechnics, 2025)

The First Non-Chordates QRFP-Like Peptide Receptor Gene in the Cephalopod Sepiella japonica: Identification, Characterization and Possible Role in Food Intake - Shuang Li; Qing Hao; Jiayin Qiu; Xu Zhou; Changfeng Chi; Libing Zheng (Journal of Ocean University of China, 2025)

Efficient bimetallic nanozyme precisely tuned by DNA for high-throughput foldable paper biosensing - Hongyan Zhang; Zhihan Wu; Haijun Lu; Zhe Hao; Wendong Liu; Fanghua Zhang; Ruizhong Zhang; Xiyan Li; Libing Zhang (Chemical Engineering Journal, 2025)

Exploring stem cell technology: Pioneering new pathways for female fertility preservation and restoration - Ningjing Li; Xinrong Du; Yuhong Zhao; Qin Zeng; Changli Han; Dongsheng Xiong; Libing He; Guohui Zhang; Weixin Liu (Reproductive Biology, 2024)

Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2024)

Biogeographic and co-occurrence network differentiation of fungal communities in warm-temperate montane soils - Libing He; Xiangyang Sun; Suyan Li; Wenzhi Zhou; Jiantao Yu; Guanyu Zhao (Science of The Total Environment, 2024)

3-ketoacyl-CoA synthase 7 from Xanthoceras sorbifolium seeds is a crucial regulatory enzyme for nervonic acid biosynthesis - Linkun Li; Chongjun Liang; Wei Zhang; Xin Zhang; Haiyan Yu; Xiaojuan Liu; Quanxin Bi; Libing Wang (Plant Science, 2024)

Cold plasma treatment delays the texture softening of apricot fruit through PAPL-PL-pectin changes - Mengpei Liu; Ge Li; Libing Zhang; Chenyang Wu; Xiaopeng Wei; Guangyuan Zhao; Lu Wang; Wei Zong (Food Bioscience, 2024)

A novel “pore-carrier transfer” strategy for preparation of porous liquids toward efficient CO2 capture - Yangyang Xin; Dechao Wang; Weirui Zhang; Fangfang Su; Jing Zhang; Yisong Liu; Wendi Fan; Xiaoqian Li; Libing Qian; Dongdong Yao; Yaping Zheng (Chemical Engineering Journal, 2024)

Multicolor luminescence of carbon Dots: From mechanisms to applications - Man Jiang; Yuzhu Sun; Mingyue Chen; Hongfei Ji; Ying Liu; Ruijie Qin; Xiyan Li; Hongling Gao; Ruizhong Zhang; Libing Zhang (Chemical Engineering Journal, 2024)

Ultrasensitive triethylamine gas sensors with ZnSe nanospheres/nest-like Cr-doped MoO3 - Xiangyun Tan; Li Wang; Xi Chen; Haoliang Zhang; Jiacheng Guo; Zhihu Dong; Libing Qian; Zhiyuan Chen; Chunqing He (Journal of Hazardous Materials, 2024)

Ultra-wide film mulching with moderate irrigation water salinity enhances cotton growth under drip irrigation in Xinjiang, China - Zhanli Ma; Jian Liu; Jinzhu Zhang; Feihu Yin; Li Guo; Yue Wen; Libing Song; Yan Zhu; Yonghui Liang; Zhenhua Wang (Field Crops Research, 2024)

Simultaneous modification of emission spectrum and trap distribution for achieving self-trapped excitons-based white afterglow - Huanxin Yang; Xiangxiang Chen; Haolin Lu; Wenda Sun; Yue Li; Yuhai Zhang; Yanjie Liang; Guankui Long; Libing Zhang; Xiyan Li (Chemical Engineering Journal, 2024)

A lightweight bladder tumor segmentation method based on attention mechanism - Xiushun Zhao; Libing Lai; Yunjiao Li; Xiaochen Zhou; Xiaofeng Cheng; Yujun Chen; Haohui Huang; Jing Guo; Gongxian Wang (Medical & Biological Engineering & Computing, 2024)

Identification and Expression Profile of a Neuropeptide LFRFamide-Like Gene During Different Stages of Gonadal Development in the Cephalopod Sepia pharaonis - Jiayin Qiu; Lianlian Sun; Shuang Li; Xu Zhou; Changfeng Chi; Libing Zheng (Journal of Ocean University of China, 2024)

Depth effects on bacterial community altitudinal patterns and assembly processes in the warm-temperate montane forests of China - Libing He; Xiangyang Sun; Suyan Li; Wenzhi Zhou; Jiantao Yu; Guanyu Zhao; Zhe Chen; Xueting Bai; Jinshuo Zhang (Science of The Total Environment, 2024)

High-purity monoclinic pyrrhotite derived from natural pyrite with excellent removal performance for Cr (VI) and its mechanism - Hao Liu; Yuxin Li; Guocheng Lv; Xin Liu; Libing Liao (Environmental Science and Pollution Research, 2024)

Multi-objective optimization of saline water irrigation in arid oasis regions: Integrating water-saving, salinity control, yield enhancement, and CO2 emission reduction for sustainable cotton production - Zhanli Ma; Yan Zhu; Jian Liu; Yanqiang Li; Jinzhu Zhang; Yue Wen; Libing Song; Yonghui Liang; Zhenhua Wang (Science of The Total Environment, 2024)

Elevated atmospheric CO2 promotes the contribution of autotrophic nitrification to N2O emissions in a typical summer maize field - Fen Ma; Yingchun Li; Ying Liu; Libing Dong; Xue Han; Xinyue Zhang; Kuo Li; Liping Guo (European Journal of Agronomy, 2024)

Meteorological to Agricultural Drought Propagation Time Analysis and Driving Factors Recognition Considering Time-Variant Characteristics - Chengguo Wu; Yin Xu; Juliang Jin; Yuliang Zhou; Boyu Nie; Rui Li; Yi Cui; Fei Tong; Libing Zhang (Water Resources Management, 2024)

Effects of Enclosure on Grassland Ecological and Economic Benefits in Northern China - Bo Hu; Qingke Wen; Fengjiang Xi; Mengyao Li; Libing Wang; Yuejuan Ren (Chinese Geographical Science, 2024)

Near-infrared electrochemiluminescence of defect-rich molybdenum disulfide quantum dots for sensitive bioanalysis - Mingyue Chen; Yuzhu Sun; Hongfei Ji; Man Jiang; Wendong Liu; Mingzheng Shao; Zhe Hao; Hongyan Zhang; Xiyan Li; Yanfeng Dang; Ruizhong Zhang; Libing Zhang (Chemical Engineering Journal, 2023)

Fouling mechanism and effective cleaning strategies for vacuum membrane distillation in brackish water treatment - Shan Wang; Yongjun You; Xingpeng Wang; Weixiong Huang; Libing Zheng; Fayong Li (Desalination, 2023)

Approximate water vertical infiltration extremum path in unsaturated soils - Jiwei Li; Yongjian Zhu; Hui Jin; Bo Zhou; Libing Han; Huabin Wang; Changfu Wei (Journal of Hydrology, 2023)

Return volatility, correlation, and hedging of green and brown stocks: Is there a role for climate risk factors? - Haohua Li; Elie Bouri; Rangan Gupta; Libing Fang (Journal of Cleaner Production, 2023)

Environmentally-friendly foam-coating synthetic strategy for fabrics with robust superhydrophobicity, self-cleaning capability and flame retardance properties - Wei Li; Libing Yang; Xiaowen Xie; Kim Hoong Ng; Feng Xu; Chan Zheng; Zhiqi Zhang; Shuhui Li; Jianying Huang; Weilong Cai; Yuekun Lai (Chemical Engineering Journal, 2023)

Electrical conductivity of magnetite-bearing antigorite upon dehydration and implications for high conductivity anomalies in forearc mantle wedges - Libing Wang; Duojun Wang; Xin Su; Zhiqing Zhang; Li Yi (Lithos, 2023)

HucMSC-EVs Facilitate In Vitro Development of Maternally Aged Preantral Follicles and Oocytes - Ying-Yi Zhang; Weijie Yang; Yi Zhang; Zhanhong Hu; Yingyan Chen; Yerong Ma; Anran Yang; Zhan Shi; Hanjing Zhou; Peipei Ren; Libing Shi; Jiamin Jin; et al. (Stem Cell Reviews and Reports, 2023)
Follicle developmental capacity and oocyte quality decline with advanced maternal age. Extracellular vesicles from human umbilical cord mesenchymal stem cells (HucMSC-EVs) act as a potential therapeutic product in the treatment of age-related ovarian dysfunction. In vitro culture (IVC) of preantral follicles is a useful method for understanding the mechanism of follicle development and is a promising means for improving female fertility. However, whether HucMSC-EVs have beneficial effects on aged follicle development during IVC has not yet been reported. Our research demonstrated that follicular development with single-addition withdrawal of HucMSC-EVs was better than that with continuous treatment with HucMSC-EVs. HucMSC-EVs facilitated the survival and growth of follicles, promoted the proliferation of granulosa cells (GCs), and improved the steroid hormone secretion of GCs during IVC of aged follicles. Both GCs and oocytes could uptake HucMSC-EVs. Moreover, we observed elevated cellular transcription in GCs and oocytes after treatment with HucMSC-EVs. The RNA sequencing (RNA-seq) results further validated that the differentially expressed genes are related to the promotion of GC proliferation, cell communication, and oocyte spindle organization. Additionally, the aged oocytes displayed a higher maturation rate, presented less aberrant spindle morphology, and expressed a higher level of the antioxidant protein Sirtuin 1 (SIRT1) after treatment with HucMSC-EVs. Our findings suggested that HucMSC-EVs can improve the growth and quality of aged follicles and oocytes in vitro through the regulation of gene transcription, which provides evidence for HucMSC-EVs as potential therapeutic reagents to restore female fertility with advanced age. Graphical Abstract

Mixed scaling deconstruction in vacuum membrane distillation for desulfurization wastewater treatment by a cascade strategy - Libing Zheng; Chenlu Li; Chun Zhang; Sai Kang; Rui Gao; Jun Wang; Yuansong Wei (Water Research, 2023)

The vertical distribution and control factor of microbial biomass and bacterial community at macroecological scales - Libing He; Xiangyang Sun; Suyan Li; Wenzhi Zhou; Zhe Chen; Xueting Bai (Science of The Total Environment, 2023)

Identification of Germline Mutations in East-Asian Young Never-Smokers with Lung Adenocarcinoma by Whole-Exome Sequencing - Fangqiu Fu; Xiaoting Tao; Zhonglin Jiang; Zhendong Gao; Yue Zhao; Yuan Li; Hong Hu; Libing Shen; Yihua Sun; Yang Zhang (Phenomics, 2023)

Celsr2 Knockout Alleviates Inhibitory Synaptic Stripping and Benefits Motoneuron Survival and Axon Regeneration After Branchial Plexus Avulsion - Lingtai Yu; Mengfan Liu; Fuxiang Li; Qianghua Wang; Meizhi Wang; Kwok-Fai So; Yibo Qu; Libing Zhou (Molecular Neurobiology, 2023)
Axotomy-induced synaptic stripping modulates survival and axon regeneration of injured motoneurons. Celsr2 is supposed to mediate homophilic interactions of neighboring cells during development, and its role in synaptic stripping remains unknow. In a model of brachial plexus avulsion, Celsr2 knockout improved functional recovery, motoneuron survival, and axon regeneration. Celsr2 was indicated to express in spinal motoneurons, excitatory and inhibitory interneurons, astrocytes, and a subset of oligodendrocytes using Celsr2 LacZ mice. Double immunostaining showed that the coverage of inhibitory and excitatory vesicles on injured motoneurons were remarkably reduced after injury, whereas more inhibitory vesicles were maintained in Celsr2 −/− mutants than control mice. In the ultrastructure, the density of inhibitory F-boutons on injured motoneurons was higher in Celsr2 −/− mutants than controls. Conditional knockout of Celsr2 in astrocytes or oligodendrocytes showed the similar axotomy-induced synaptic withdrawal to the control. RNAseq of injured spinal samples identified 12 MHC I molecules with significant changes between Celsr2 −/− and control mice. After injury, expression of MHC I surrounding injured motoneurons was increased, particularly high in Celsr2 −/− mutants. In conclusion, Celsr2 knockout enhances MHC I signaling, alleviates inhibitory synaptic stripping cell-autonomously, and contributes to motoneuron survival and regeneration, and Celsr2 is a potential target for neural repair.

Assessing the impact of seasonal freezing and thawing on the soil microbial quality in arid northwest China - Rui Zong; Zhenhua Wang; Wenhao Li; Olusola O. Ayantobo; Haiqiang Li; Libing Song (Science of The Total Environment, 2023)

Effective pH-responsive nanocarrier based on the anisotropic surfaces of halloysite nanotubes for controlled drug release - Xinyu Lei; Yi Zhou; Xianhao Liu; Lingchang Kong; Libing Liao; Yuxin Li; Meng Liu; Lintao Tian; Wenxiu Rao; Guocheng Lv (Applied Clay Science, 2023)

Celsr3 Inactivation in the Brainstem Impairs Rubrospinal Tract Development and Mouse Behaviors in Motor Coordination and Mechanic-Induced Response - Boli Chen; Fuxiang Li; Bin Jia; Kwok-Fai So; Ji-An Wei; Yuchu Liu; Yibo Qu; Libing Zhou (Molecular Neurobiology, 2022)
Inactivation of Celsr3 in the forebrain results in defects of longitudinal axonal tracts such as the corticospinal tract. In this study, we inactivated Celsr3 in the brainstem using En1-Cre mice ( Celsr3 cKO) and analyzed axonal and behavioral phenotypes. Celsr3 cKO animals showed an 83% reduction of rubrospinal axons and 30% decrease of corticospinal axons in spinal segments, associated with increased branching of dopaminergic fibers in the ventral horn. Decreases of spinal motoneurons, neuromuscular junctions, and electromyographic signal amplitude of the biceps were also found in mutant animals. Mutant mice had impaired motor coordination and defective response to heavy mechanical stimulation, but no disability in walking and food pellet handling. Transsynaptic tracing demonstrated that rubrospinal axons synapse on spinal neurons in the deep layer of the dorsal horn, and mechanical stimulation of hindpaws induced strong calcium signal of red nuclei in control mice, which was less prominent in mutant mice. In conclusion, Celsr3 regulates development of spinal descending axons and the motor network in cell and non-cell autonomous manners, and the maturation of the rubrospinal system is required for motor coordination and response to mechanical stimulation.

Retraction Note to: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2022)

Comparative transcriptome combined with morpho-physiological analyses revealed candidate genes potentially for differential cold tolerance in two contrasting apricot (Prunus armeniaca L.) cultivars - Dan Yu; Xiaojuan Liu; Yifan Cui; Quanxin Bi; Yang Zhao; Dongxing Li; Haiyan Yu; Libing Wang (Trees, 2020)

Antibacterial and antiparasitic activities analysis of a hepcidin-like antimicrobial peptide from Larimichthys crocea - Libing Zheng; Yuan Li; Jun Wang; Ying Pan; Jia Chen; Weiqiang Zheng; Longshan Lin (Acta Oceanologica Sinica, 2020)

Toxic element (As and Hg) content and health risk assessment of commercially available rice for residents in Beijing based on their dietary consumption - Libing Li; Huashuai Feng; Junxiao Wei (Environmental Science and Pollution Research, 2020)

Detection of FOXO1 break-apart status by fluorescence in situ hybridization in atypical alveolar rhabdomyosarcoma - Libing Fu; Yaqiong Jin; Chao Jia; Jie Zhang; Jun Tai; Hongbin Li; Feng Chen; Jin Shi; Yongli Guo; Xin Ni; Lejian He (Science China Life Sciences, 2017)

RETRACTED ARTICLE: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2017)

The Potential Mutation of GAK Gene in the Typical Sporadic Parkinson’s Disease from the Han Population of Chinese Mainland - Jie Zhang; Hanyi Zeng; Lei Zhu; Libing Deng; Xin Fang; Xia Deng; Huiting Liang; Chunyan Tang; Xuebing Cao; Yi Lu; Jiao Li; Xiao Ren; et al. (Molecular Neurobiology, 2016)

Potential submarine geologic hazards at the entrance of the Pearl River Estuary in the northern South China Sea - Zhiqiang Zhang; Zhiqiang Wei; Huizhong He; Wei Wei; Libing Qian; Tuanjie Li (Journal of Ocean University of China, 2016)

Migration of photoinitiators from paper to fatty food simulants: experimental studies and model application - Bo Han; Li Ding; Rongxin Su; Lei Chen; Libing Wang; Wei Qi; Zhimin He (Food Additives & Contaminants: Part A, 2016)

Rapid and sensitive detection of canine parvovirus type 2 by recombinase polymerase amplification - Jianchang Wang; Libing Liu; Ruiwen Li; Jinfeng Wang; Qi Fu; Wanzhe Yuan (Archives of Virology, 2016)

Molecular cloning of vasa gene and the effects of LHRH-A on its expression in blue tilapia Oreochromis aureus - Jun Xiao; Yongju Luo; Libing Chen; Li Yang; Yulin Huang; Zhongbao Guo; Enyan Guo; Zhanyang Tang; Ming Zhang; Xi Gan (Fish Physiology and Biochemistry, 2013)

Inference of reference conditions for nutrient concentrations of Chaohu Lake based on model extrapolation - Yuliang Zhou; Juliang Jin; Li Liu; Libing Zhang; Jun He; Zhesun Wang (Chinese Geographical Science, 2013)

Metabonomics Approaches and the Potential Application in Foodsafety Evaluation - Hua Kuang; Zhe Li; Chifang Peng; Liqiang Liu; Liguang Xu; Yingyue Zhu; Libing Wang; Chuanlai Xu (Critical Reviews in Food Science and Nutrition, 2012)

An improved Markov chain model based on autocorrelation and entropy techniques and its application to state prediction of water resources - Ping Zhou; Yuliang Zhou; Juliang Jin; Li Liu; Zongzhi Wang; Liang Cheng; Libing Zhang (Chinese Geographical Science, 2011)

Identification of the Binding Domain of Signal-Transduction-Related Proteins on c-Mpl - Limin Yang; Libing Feng; Li Huang; Weiguo Zhou; Min Wan; Shouyuan Zhao; Changben Li (Biochemical Genetics, 2003)

Screen and identification of proteins interacting with ADAM19 cytoplasmic tail - Li Huang; Libing Feng; Limin Yang; Weiguo Zhou; Shouyuan Zhao; Changben Li (Molecular Biology Reports, 2002)